A computer-aided design technology for manufacturing rubber and metal products - Становський, Олександр Леонідович; Лєбедєва, Олена Юріївна; Мохаммед Алі, Абу Шена Осама; Красножон, Олександр Миколайович; Швець, Павло Степанович (Eastern-European Journal of Enterprise Technologies, 2015)
The study deals with the problems of a computer-aided design technology for the production of technical composite articles consisting of anisotropic materials with significantly different mechanical properties. The study is aimed at reducing the pre-production stage and increasing the quality of industrial products through the development and implementation of an improved method of optimizing CAD-T for rubber and metal products. The method is based on identifying and avoiding possible bifurcation points at the stage of computer-aided design of shock absorption equipment, which is a composite system of elements with significantly different properties. We have analyzed the existing problems and methods of computer-aided design of rubber and metal composite products whose components have different properties. The devised CAD-T that is based on the phase portraits of the studied processes optimizes the technology parameters of the production of shock absorption equipment. Our computer-aided laboratory tests of the findings and production tests of the CAD-T gave positive technical effects. The devised CAD-T has laid the basis for technically and economically beneficial pre-production of rubber and metal shock absorbers at the Odessa Rubber Factory.